Improvement of the bearing of soil by using lime – rice husk ash - Agus Setyo Muntohar (Geotechnical and Geoenvironmental Engineering i, 2002)
Rice husk ash is a potential pozzolanic material that can be used for stabilizing agent in the mixture with lime. This paper presents the results of studies in the use of rice husk ash (RHA), yield from rice husk combustion in Yogyakarta - Indonesia, to improve the bearing of soft soil. Laboratory tests have been conducted in this study, such as index properties, compaction, and California Bearing Ratio (CBR) tests. The results of the study show that lime and RHA can increase the bearing capacity of the subgrade. The bearing of treated soils with lime – RHA mixture enhanced multiplies associated with curing time. On the other side, the swell of expansive soil decreased to relatively non– swelling.